Low Power Key Management Protocol for Wireless Sensor Network (International Journal of Advanced Research in Computer Science, 2017)
Wireless sensor networks are highly sensitive to the energy consumed as they consume more power in communication and routing the data across each other also The energy cost of transmitting 1 Kb a distance of 100 m is approximately the same as that for the executing 3 million instructions by 100 million instructions per second/W processor. In the current work the authors have thought upon the energy aspects such that the un-scaled i.e raw value of the data shall be used instead of the converted value. The material defects and aging factors will also be used to hide the actual value of the data. Also complete use of symmetric key ensures that power saving happens at every aspect. The use of swarm intelligence for the generation of the keys also provides dynamic security. Several symmetric-key pre-distribution protocols have been investigated recently to establish secure links between sensor nodes, but most of them are not scalable due to their linearly increased communication and key storage overheads. Furthermore, existing protocols cannot provide sufficient security when the number of compromised nodes exceeds a critical value. To address these limitations, we propose an improved key management mechanism for large-scale wireless sensor networks. A highly unexposed area of non-scaled data has been chosen as one of the parameters along with an innovative method called graph based key management integrated with each others to solve this problem.Â Keywords: Key management, Wireless sensor networks, cryptography , symmetric key algorithms, Scaling of sensors.